Assessing the impact of mobile technological innovation on maternal healthcare in South Africa - Matee, Misha Govind (My University, 2020)
Background: Maternal mortality is a significant public health issue in developing countries due to its shocking magnitude and lower declining pattern. Identifying determinants and designing intervention will have an important role to overcome the problem. Ending preventable maternal mortality remains one of the world’s most critical challenges despite significant progress over the past decade. These deaths are primarily from preventable causes before, during and after the time of giving birth. (Boerma, et al., 2015) Creative use of new mobile and wearable health information and sensing technologies (mHealth) has the potential to reduce the cost of health care and improve well-being in numerous ways. (Kumar, et al., 2013) The rapid growth in access to mobile phones and networks in Africa has created an opportunity for mHealth programs to impact the health of Africans positively. mHealth programs have the potential to contribute to innovative solutions to address health system challenges including (1) disparities in access to health services; (2) inadequacies of health infrastructure; (3) limited human resources for health; (4) cost to the individual of accessing health services; and (5) challenges in health financing. (African Strategies for Health (ASH), 2016) Therefore this study aimed to identify the correlates of mobile technology and maternal mortality in developing countries. Method: This research report conducted used national and international databases of health metrics from 2011 to 2019. Using aggregates of health indicator data from Statistics South Africa (STATSSA), the World Health Organisation (WHO), World Bank, United Nations Development Programme (UNDP) and United Nations International Children's Emergency Fund (UNICEF) databases. Momconnect and Mum & Baby data were collected from Vodacom South Africa, the National Department of Health (NDoH) and Praekelt. The dependent variable was the maternal mortality ratio (MMR). In contrast, the independent variable was the numbers of subscribers for Momconnect and Mum & Baby, two national maternal mobile healthcare applications in South Africa. Data was compiled in excel and analysed using correlation tests and regression analysis. Results: The maternal mortality ratio in South Africa is high. A significant relationship between the maternal mortality ratio and the adoption of mobile healthcare applications was observed. There were an inverse and significant correlation between the maternal mortality ratio and the diffusion of mobile technology. Conclusion: The maternal mortality ratio is correlated with mobile technology.
A research report submitted in fulfilment of the requirements for the degree of Masters of Management in the Field of Innovation Studies (MMIS) to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, School of Governance, Johannesburg, 2020
Keywords: UCTD; Maternal Mortality Ratio (MMR) in South Africa; Infant Mortality Rate (IMR) in South Africa; Causes of maternal deaths in South Africa; Maternal healthcare in South Africa; Technology in Maternal Healthcare in South Africa; Mobile healthcare applications; SDG-3: Good health and well-being